Immune evasion of Borrelia burgdorferi by acquisition of human complement regulators FHL-1/reconectin and Factor H - Kraiczy, Peter; Skerka, Christine; Kirschfink, Michael; Brade, Volker; Zipfel, Peter F. (European journal of immunology, 2001)
To understand immune evasion mechanisms of Borrelia burgdorferi we compared serum-resistant B. afzelii and serum-sensitive B. garinii isolates for their capacity toacquire human complement regulators. Here we demonstrate that the two borrelial genospecies show different binding of the two important human complement regulators, FHL-1/reconectin and Factor H. All serum-resistant B. afzelii isolates bound FHL-1/reconectin and also Factor H, and all analyzed serum-sensitive B. garinii isolates showed no or a significantly lower binding activity. Using recombinant deletion mutants, the binding domains were localized to the C terminus of FHL-1/reconectin to short consensus repeats 5-7. The borrelial binding proteins were located in the surface of the bacteria as demonstrated by immunofluorescence staining of intact, serum-exposed bacteria and by enrichment of outer membrane proteins. The surface-attached complement regulators maintained complement regulatory activity as demonstrated in a cofactor assay. By ligand blotting two different borrelial binding proteins were identified that were responsible for the surface attachment of FHL-1/reconectin and Factor H. These borrelial complement regulators acquiring surface proteins (CRASP) were further characterized as either CRASP-1, a 27.5-kDa molecule which preferentially binds FHL-1/reconectin and which was present in all serum-resistant borreliae, or CRASP-2, a 20/21-kDa protein which interacts preferentially with Factor H and the expression of which was more restricted, being detected in four of the six isolates analyzed. In summary, we describe a new immune evasion mechanism of B. burgdorferi, as these bacteria acquire human complement regulators to control complement activation on their surface and to prevent formation of toxic activation products.
Gesehen am 17.02.2021